Understanding the building of professional identities with the LEGO® SERIOUS PLAY® method using situational mapping and analysis. Issue 1 (4th September 2019) - Hayes, Catherine; Graham, Yitka
Abstract : Purpose: The purpose of this paper is to explore the notion that social constructionist approaches to learning, which a building with the hands provides, is a "technique that leverages the potential of the hand-mind dynamic" as historically reported in the extant published literature. Design/methodology/approach: The use of the LEGO® SERIOUS PLAY® (LSP) method in the context of transformative learning in Higher Education was used to drive a Situational analysis with sixteen postgraduate nursing students, from African learning contexts. This methodological approach was used to specifically explore their identity as learners and then to facilitate processes of critical introspection on social constructivist learning opportunities. Findings: Students' perceived LSP permitted a deeper level of critical introspection on their transformative learning journeys than alternative approaches, such as written discourse or extended narratives, could have provided. They also perceived that a major benefit of using the LSP method was that it enabled them to understand and articulate their stories more easily than if they verbally reported them first. Research limitations/implications: The sampling the authors used was purposive and reflective of the Nigerian background of our research participants, who study at the University of Sunderland. Practical implications: LSP was perceived as an effective vehicle for the facilitation of reflection and self-awareness, which consequently contribute to students' capacities to function at a metacognitive level. This has the potential to contribute to authentic transformative learning. Academic learning at postgraduate level hinged on the capacity of students to develop a pragmatic and working knowledge of what acknowledging their epistemic cognition entailed. Originality/value: The methodological approach implemented in this paper provides a unique means of harnessing a now common gamification technique in pedagogic practice.